United European Gastroenterology (UEG) and European Society for Neurogastroenterology and Motility (ESNM) consensus on functional dyspepsia. Issue 9 (29th September 2021) - Wauters, Lucas; Dickman, Ram; Drug, Vasile; Mulak, Agata; Serra, Jordi; Enck, Paul; Tack, Jan; ,; Accarino, Anna; Barbara, Giovanni; Bor, Serhat; Coffin, Benoit; et al.
Abstract: Background: Functional dyspepsia (FD) is one of the most common conditions in clinical practice. In spite of its prevalence, FD is associated with major uncertainties in terms of its definition, underlying pathophysiology, diagnosis, treatment, and prognosis. Methods: A Delphi consensus was initiated with 41 experts from 22 European countries who conducted a literature summary and voting process on 87 statements. Quality of evidence was evaluated using the grading of recommendations, assessment, development, and evaluation (GRADE) criteria. Consensus (defined as >80% agreement) was reached for 36 statements. Results: The panel agreed with the definition in terms of its cardinal symptoms (early satiation, postprandial fullness, epigastric pain, and epigastric burning), its subdivision into epigastric pain syndrome and postprandial distress syndrome, and the presence of accessory symptoms (upper abdominal bloating, nausea, belching), and overlapping conditions. Also, well accepted are the female predominance of FD, its impact on quality of life and health costs, and acute gastrointestinal infections, and anxiety as risk factors. In terms of pathophysiological mechanisms, the consensus supports a role for impaired gastric accommodation, delayed gastric emptying, hypersensitivity to gastric distention, Helicobacter pylori infection, and altered central processing of signals from the gastroduodenal region. There is consensus that endoscopy is mandatory for establishing a firm diagnosis of FD, but that in primary care, patients without alarm symptoms or risk factors can be managed without endoscopy. There is consensus that H. pylori status should be determined in every patient with dyspeptic symptoms and H. pylori positive patients should receive eradication therapy. Also, proton pump inhibitor therapy is considered an effective therapy for FD, but no other treatment approach reached a consensus. The long‐term prognosis and life expectancy are favorable. Conclusions and Inferences: A multinational group of European experts summarized the current state of consensus on the definition, diagnosis and management of FD. Key summary: Current knowledge Functional dyspepsia is one of the most common conditions encountered in clinical practice. There is a lack of guidance for clinicians in guiding diagnosis and treatment of this prevalent condition. No treatments are currently approved for the treatment of functional dyspepsia in Europe. What is new here A Delphi panel consisting of 41 experts from 22 European countries established the level of consensus on 87 statements regarding functional dyspepsia. The statements reaching consensus serve to guide clinicians in recognizing, diagnosing and treating FD in clinical practice. Endoscopy is mandatory for establishing a firm diagnosis of functional dyspepsia D, but in primary care patients without alarm symptoms or risk factors can be managed without endoscopy. Helicobacter pylori status should be determined in every patient with dyspeptic symptoms and H. Pylori positive patients should receive eradication therapy. Proton pump inhibitor‐therapy is considered an effective therapy for FD, but no other treatment approach reached consensus support.